Estruturas socioambientais e os múltiplos espaços urbanos de Aracaju/SE - Santos, Jadson de Jesus (2019)
Cities are the habitat of man and it is in them where individual and collective formations take place within society. The urbanization of spaces, formerly natural, transformed, over time, the city as the place favorable to meet the needs of the man's life so that the necessary quality of life can be achieved. Aracaju, capital of the State of Sergipe, as well as in other Brazilian cities, does not escape the rule. The Sergipe capital has undergone processes of transformation of the natural environment since its foundation, from the construction of new urban spaces in the landfills made on the mangroves, restingas and marshes. Since then, it is possible to observe the differences given in the urban sprawl of Aracaju influenced by the economic power wielded by wealthy population, whereas for the poor, tries to drive them these prime areas, leaving them the unplanned neighborhoods and without same infrastructure found in noble areas, necessary for the quality of life. In this way, it is possible to perceive criteria of investments in the urban spaces of Aracaju in which there are several, but it is the economic power that has a main and determinant role to the execution of the modifications of the urban spaces. The problematic aspect is when investments in specific environmental areas are reduced and sometimes neglected. That said, the execution of the research presented was given from the use of techniques of quantitative and qualitative analysis, based on the bibliometrics as a means of conceptual and bibliographical training to later present the thesis from the landscape analysis, and supported by research documentary. For the implementation of research and organization of the thesis, had as general objective: to analyze the environmental infrastructure considering the dynamics of the city of Aracaju to relate planning, management and functionality of urban spaces and for that we defend the thesis that the spatial distribution of equipment urban socialization with the environment in the city of Aracaju privileges the most noble areas of the city. In this sense, it became clear that the social and environmental areas of Aracaju are different according to its location, which need to be reviewed by managers when implementing investments in infrastructure (squares, edges and parks) that are harmonious for the city must be accessible to all, regardless of the economic power that each one has. In this way, the spaces should be built in harmony with the natural environment, still existing in the city, so that these spaces can be preserved/maintained so that Aracaju can (dis)continuously engage for the entire population.